Strategi Peningkatan Kinerja Usaha Lokal Melalui Pengelolaan Keuangan, Budaya Kerja, dan Digital Marketing - Andrianto Prasetya Nugroho; Zulfa Zakiatul Hidayah; Sunita Dasman; Dwi Epty Hidayaty; Annisa Aulia Aryani (Lembaga Pengembangan Kinerja Dosen, 2026)
Breastfeeding self-efficacy is an important psychological factor that affects the sustainability of breastfeeding. Low Self-Efficacy can contribute to early cessation of breastfeeding. This community-based education activity aims to improve the Self-Efficacy of breastfeeding through video-based lactation education for postpartum mothers in the working area of the Leuwidamar Health Center, Lebak Regency, in 2026. A total of 13 postpartum mothers were involved in the activity. The implementation stages include initial measurement using the 14-item Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF), 15-20 minutes of education about the benefits of breast milk, position and attachment, lactation management, and handling of breastfeeding problems. The educational video was shared via WhatsApp so that it could be replayed, then measured again one week after the intervention. The results showed an increase in the average score of BSES-SF from 35.38 (SD 1,261; range 34–38) to 65.92 (SD 3,068; range 60–70). The paired t-test showed a statistically significant change (mean difference of 30.538; p=0.0001). Video-based lactation education is feasible as a promotive strategy in primary health services and has the potential to strengthen maternal confidence in breastfeeding. Further implementation needs to be complemented by individualized counseling as well as evaluation of long-term breastfeeding practices.